2021
DOI: 10.3390/md19040183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Seaweed Extracts to Pigs until d35 Post-Weaning on Performance and Aspects of Intestinal Health

Abstract: The objective of this study was to examine the effects of feeding laminarin (LAM) and fucoidan (FUC) enriched seaweed extracts up to d35 post-weaning on measures of animal performance, intestinal microbial and transcriptome profiles. 75 pigs were assigned to one of three groups: (1) basal diet; (2) basal diet + 250 ppm fucoidan; (3) basal diet + 300 ppm laminarin with 7 replicates per treatment group. Measures of performance were collected weekly and animals sacrificed on d35 post-weaning for the sampling of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Indeed, diet is a major determinant of the gut microbiome composition [48], which has a major role on the health of the recently weaned piglet. This was recently demonstrated in piglets fed with seaweed extracts [49].…”
Section: Effect Of Lysozyme Supplementation Within Spirulina Dietsmentioning
confidence: 65%
“…Indeed, diet is a major determinant of the gut microbiome composition [48], which has a major role on the health of the recently weaned piglet. This was recently demonstrated in piglets fed with seaweed extracts [49].…”
Section: Effect Of Lysozyme Supplementation Within Spirulina Dietsmentioning
confidence: 65%
“…Fucoidan, for example, has higher antioxidant capacity compared to laminarin due to the higher degree of sulphate groups and positive charge [ 68 ]. As such, they have been used as an alternative to antibiotics as growth promotors [ 69 , 70 ] and in meat-derived product formulations to enhance shelf-life [ 71 ]. Moroney et al [ 61 ] have demonstrated that the dietary inclusion of polysaccharides from Laminaria digitate —laminarin (500 mg/kg) and fucoidan (420 mg/kg)—decreased lipid oxidation in the longissimus dorsi muscle of pigs.…”
Section: Effect Of Dietary Seaweeds On Pork Meat Qualitymentioning
confidence: 99%
“…Laminarin supplementation elevates villus height in the duodenum and jejunum, improves performance, and prevents post-weaning intestinal dysfunction. Laminarin exerts a positive influence on intestinal health through alterations in the gastrointestinal microbiome ( 32 , 33 ). The results from research evaluating phytogenic additives as growth performance enhancers are variable ( 34 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%